Kepemimpinan Perguruan Tinggi dalam Pengembangan Profesionalisme Dosen - Saefrudin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The development of lecturer professionalism in this research refers to education and training based on Law No. 14 of 2005 concerning the duties and functions of lecturers in implementing the tri dharma of higher education, responding to social change, and the era of globalization. This research aims to analyze and discover the education Leadership Style in Developing Lecturer Professionalism at UNHASY Jombang, Higher Education Leadership Strategy in Developing Lecturer Professionalism at UNHASY Jombang Lecturer Responses to Developing Lecturer Professionalism at UNHASY Jombang This research uses a qualitative approach, type of case study with a multisite design (case study). Data collection techniques use in-depth interviews, participant observation, and documentation. Data analysis includes single-case and cross-case data analysis, using the Miles Huberman model of data analysis techniques: data presentation, data reduction, and concluding. Data checking for data validity is carried out through credibility, transferability, dependability, and confirmability. The results of this research are as follows; The leadership style applies formal, charismatic symbolic leadership, the indicators are recognition of legality, clear direction of vision, knowing one's strengths, and giving authority to subordinates. Leaders behave as: communicative, motivative, visionary educators, managers, and leaders; who can build an optimistic spirit, Leadership strategies through persuasive approaches, communication, motivators, delegation, education, training to internalize Islamic boarding school values, improving welfare, partnerships, optimizing lecturer administration SOP systems and infrastructure; building trust to produce subordinate staff who have loyalty and integrity; Response to the development of lecturer professionalism carried out by leaders; first, the lecturer's response supports the indicators: loyalty, need for achievement, doing the best, work is worship; secondly, the lecturer's response is not supportive, the indicator is that they are not happy: it is difficult to accept change, transition, maintaining bad old traditions, low levels of increasing one's potential. Based on the substantive findings above, the formal findings in this research are